2014
DOI: 10.11118/actaun200957050183
|View full text |Cite
|
Sign up to set email alerts
|

The influence of linseed oil and fish oil diet supplements to the fatty acid spectrum of common carp (Cyprinus carpio L.) muscle

Abstract: Effect of addition 6% of linseed oil (designated L06), 6% and 10% of fish oil (R06 and R10) to feed on the fatty acid spectrum of common carp (Cyprinus carpio L.) was investigated. The basic feedmixture which was used as a control variant (K – 34% protein; 9% fat) and the three with oil addition (L06, R06 and R10) were fed to carp fingerling (43.25 g average weight) for 60 days – from 23rd April to 20th June. Before that the fish were fed for 2 month by whey grain and commercial feed for carp fingerling in pon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…Several studies have shown that total replacement of FO with vegetable oils, including RO in diets of cyprinid fish species, has no negative effects on fish growth and growth parameters (Turchini et al, 2007;Kukačka et al, 2009;Zakęś et al, 2010). In agreement with the previous studies, the present experiment showed no negative effect of total inclusion of RO instead of FO on production parameters and growth of common carp reared in cages under natural atmospheric conditions.…”
Section: Production Performancesupporting
confidence: 94%
See 1 more Smart Citation
“…Several studies have shown that total replacement of FO with vegetable oils, including RO in diets of cyprinid fish species, has no negative effects on fish growth and growth parameters (Turchini et al, 2007;Kukačka et al, 2009;Zakęś et al, 2010). In agreement with the previous studies, the present experiment showed no negative effect of total inclusion of RO instead of FO on production parameters and growth of common carp reared in cages under natural atmospheric conditions.…”
Section: Production Performancesupporting
confidence: 94%
“…Thus, the SFA, ARA, EPA, and the total n-3 PUFA were utilised to a higher extent by the fish fed the FO and HP diets compared to the RO and LP groups, as previously reported for cyprinid omnivorous fish species (Pozernick and Wiegand, 1997;Turchini et al, 2007;Kukačka et al 2009;Zakęś et al, 2010;Sun et al, 2011). DHA appeared to be slightly utilised in the FO and HP groups but was stored in the muscle of the RO and LP groups.…”
Section: Fatty Acid Composition Of Common Carp Filletssupporting
confidence: 56%